Early husbandry practices in highland areas during the Neolithic: the case of Coro Trasito cave (Huesca, Spain) - Navarrete, Vanessa; Viñerta, Angel; Clemente-Conte, Ignacio; Gassiot, Ermengol; Rey Lanaspa, Javier; Saña, Maria (Frontiers in Environmental Archaeology, 2023)
Research on animal management strategies in high mountain areas during the early Neolithic (5,700–4,500 cal BC) has been conditioned by the presumption that human occupations in highland areas had a prominent seasonal character and the economic practices focused mainly on the exploitation of wild resources. The results obtained in the framework of research developed recently on settlement dynamics during the early Neolithic in the highland areas indicate the existence of relatively permanent occupations and the exploitation of domestic resources. Regarding livestock, the role of caprine transhumance in highland areas has been highlighted traditionally, conferring a marginal role to husbandry activities and emphasizing principally the temporary maintenance of herds of sheep and goats. In this study, we use the archaeozoological data and δ13C and δ15N stable isotopes composition of the faunal bones collagen to characterize the husbandry practices in Coro Trasito cave (Huesca, Spain). The results obtained demonstrated the presence of diverse herd foddering strategies within husbandry practices characterized by taxonomic diversity and multipurpose exploitation suggests that during the Neolithic, Coro Trasito cave played a more complex role than sheepfold. Moreover, the presence of the four main domestic species indicates the adaptation of herds of Coro Trasito to the cave environment, flocks with diverse dietary needs and reproductive behaviors. The results are discussed with an integrated analysis of the data related to animal management strategies in highland areas (more than 1,500 m. asl) during the early Neolithic, in particular in the central Pyrenees area. This study offers new elements to study the complexity of neolithization processes in the central Pyrenees and how these areas were quickly integrated into a broader economic system.